Methods of Teaching Harmony of Weight and Content in Rubai - Meyliyeva Nasiba Tolmas qizi (Genius Journals, 2023)
In this article, methods of teaching the weight characteristics of the rubai written by Alisher Navai, presented in the textbook “Literature” of the 8th – 10th grade, have been developed
Keywords: Textbook; “Literature”; aruz; prosody